Peran BMT Nuansa Umat Dalam Memberdayakan Ekonomi Masyarakat Di Kecamatan Grujugan Kabupaten Bondowoso - Iit Hoiriyatul Hasanah; M. Saleh; Ahmad Roziq (UPT Penerbitan Universitas Jember, 2023)
Financial institutions have a very big role in developing people's growth in the industrial era. Among them is BMT. BMT is a business entity that has a legal entity as a cooperative and must comply with the rules regarding cooperatives. This study aims to determine the role of BMT NU Grujugan Branch through community economic empowerment programs and the community's perspective on the role of BMT Nuansa Ummat Grujugan Branch. The type of method used in this research is a qualitative method with a field research approach. Data collection in this study was carried out through observation, interviews, and documentation techniques. The informant determination technique is Snowball sampling. Informants in this study included the head of the BMT NU branch, the financing department, the savings section, customers who took financing and the recipients of social funds. The findings of this study show that the role of BMT Nuansa Ummat Grujugan Branch in empowering the community's economy is very high, covering several things including operational activities carried out in accordance with sharia principles, distancing the community from non-Islamic economic practices, as intermediaries between shohibul maal and the duafa/mudharib in terms of collecting and developing social funds.